Max Parra, Writing Pancho Villa's revolution. Rebels in the literary imagination of Mexico. University of Texas, Austin, 2005. - Chavarín, Marco Antonio (El Colegio de México, 2007)
Se reseñó el libro: Writing Pancho Villa's revolution. Rebels in the literary imagination of Mexico.